1967
DOI: 10.1126/science.156.3773.374
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Variability of Cosmic X-Ray Sources

Abstract: At least 30 discrete cosmic x-ray sources have been detected thus far. The distribution is concentrated toward the galactic plane, and most of the sources are believed to lie within 2 kiloparsecs of the sun. It is estimated that the average luminosity of the observed sources is about 5 x 10(36) ergs per second and that the entire galaxy contains about 1250 such sources. Comparisons of fluxes observed over the course of the past 2 years reveal that many sources are highly variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 10 publications
1
47
0
Order By: Relevance
“…GX 17+2 is one of strongest Galactic X-ray sources, and was detected in the sixties (e.g., Friedman et al 1967). Simultaneous X-ray and radio observations, performed by White et al (1978), did not show the presence of significant radio emission, but revealed correlated X-ray intensity and spectral variations similar to those already observed from Sco X-1.…”
Section: Gx 17+2mentioning
confidence: 70%
“…GX 17+2 is one of strongest Galactic X-ray sources, and was detected in the sixties (e.g., Friedman et al 1967). Simultaneous X-ray and radio observations, performed by White et al (1978), did not show the presence of significant radio emission, but revealed correlated X-ray intensity and spectral variations similar to those already observed from Sco X-1.…”
Section: Gx 17+2mentioning
confidence: 70%
“…The neutron star LXMB Serpens X-1 was discovered in 1965 (Friedman et al 1967). Being a persistent, bright X-ray source, Serpens X-1 has been observed with major X-ray missions including Einstein (Vrtilek et al 1986), ASCA (Asai et al 2000), EXOSAT (Seon & Min 2002), BeppoSAX (Oosterbroek et al 2001), INTEGRAL (Masetti et al 2004), XMM-Newton (Bhattacharyya & Strohmayer 2007), Suzaku (Cackett et al 2008(Cackett et al , 2010, and recently with NuSTAR (Miller et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 17 shows the source Norma XR-2 at 15 hr, 32minr.a., -57° dec. This source was first identified in a rocket survey (Friedman et al, 1967), observed from a balloon by Lewin and Clark (Lewin et al, 1968b) and was previously identified erroneously with Lupus XR-1 in a UCSD preprint . No significant change was observed in this The variable X-ray source Centaurus XR-2 has also been observed by the OSO-III.…”
Section: Id 4 -mentioning
confidence: 97%